Innate and Adaptive Immunity Alterations in Metabolic Associated Fatty Liver Disease and Its Implication in COVID-19 Severity - Lamadrid, Patricia; Alonso-Peña, Marta; San Segundo, David; Arias-Loste, Mayte; Crespo, Javier; Lopez-Hoyos, Marcos (Frontiers in Immunology, 2021)
The coronavirus infectious disease 2019 (COVID-19) pandemic has hit the world, affecting health, medical care, economies and our society as a whole. Furthermore, COVID-19 pandemic joins the increasing prevalence of metabolic syndrome in western countries. Patients suffering from obesity, type II diabetes mellitus, cardiac involvement and metabolic associated fatty liver disease (MAFLD) have enhanced risk of suffering severe COVID-19 and mortality. Importantly, up to 25% of the population in western countries is susceptible of suffering from both MAFLD and COVID-19, while none approved treatment is currently available for any of them. Moreover, it is well known that exacerbated innate immune responses are key in the development of the most severe stages of MAFLD and COVID-19. In this review, we focus on the role of the immune system in the establishment and progression of MAFLD and discuss its potential implication in the development of severe COVID-19 in MAFLD patients. As a result, we hope to clarify their common pathology, but also uncover new potential therapeutic targets and prognostic biomarkers for further research.